2021
DOI: 10.12669/pjms.37.4.3986
|View full text |Cite
|
Sign up to set email alerts
|

Clinical observation of thrombolytic effect of alteplase combined with butylphthalide in patients with acute anterior circulation cerebral infarction

Abstract: Objective: This study aims to evaluate the clinical effect of alteplase combined with butylphthalide in treating patients with acute anterior circulation cerebral infarction. Methods: Retrospective study methods were used. Eighty patient cases with acute anterior circulation cerebral infarction treated in Baoding First Central Hospital, China from January 2018 to December 2020 were randomly and averagely divided into two groups. Patients in the two groups were given symptomatic treatment. Patients in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Stroke seriously affects the quality of life of patients and places a heavy burden on society and families due to its high incidence, disability, recurrence, and poststroke depression [ 7 ]. The outcome of acute stroke determines the patient's prognosis, and poststroke depression is the most common mental health problem [ 8 , 9 ]. The low rate of diagnosis and treatment of poststroke depression in China has seriously affected the recovery of stroke patients, thus increasing the recurrence rate and mortality of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke seriously affects the quality of life of patients and places a heavy burden on society and families due to its high incidence, disability, recurrence, and poststroke depression [ 7 ]. The outcome of acute stroke determines the patient's prognosis, and poststroke depression is the most common mental health problem [ 8 , 9 ]. The low rate of diagnosis and treatment of poststroke depression in China has seriously affected the recovery of stroke patients, thus increasing the recurrence rate and mortality of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Butylphthalide, a compound extracted from parsley, has the effect of ameliorating cerebrovascular microcirculation and promoting platelet aggregation. It also inhibits excitatory amino acids from damaging the cholinergic nervous system 15 , and plays an important role in multiple stages of cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Butylphthalide can also significantly improve neurological functions of patients with brain injury [17], improve micro-circulation and blood flow in the ischemic brain area, increase the number of capillaries in the blood area, reduce the area of ischemic infarction, relieve brain edema, and inhibit nerve cell decay among other effects [6,18,22]. Numerous studies have proven that butylphthalide has a good therapeutic effect on cerebral infarction, providing good safety [1,13,17]. It was approved to be mar- The present study showed that the NIHSS score of the combined group was lower than that of the alteplase group after treatment, indicating that combined butylphthalide treatment can effectively improve patients' central nerve damage.…”
Section: Discussionmentioning
confidence: 99%